2014
DOI: 10.1111/vec.12145
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of evidence on veterinary viscoelastic testing Part 4: Definitions and data reporting

Abstract: Objective To systematically examine evidence surrounding definitions and reporting of data for viscoelastic testing in veterinary medicine. Design Standardized, systematic evaluation of the literature, categorization of relevant articles according to level of evidence and quality, and development of consensus on conclusions for application of the concepts to clinical practice. Setting Academic and referral veterinary medical centers. Results Databases searched included Medline, CAB abstracts, and Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 110 publications
(182 reference statements)
3
89
0
2
Order By: Relevance
“…In this previous study, the 4 measured parameters and 5 calculated indices (maximal clot elasticity, G, TPI, global index, and coagulation index) were evaluated to establish their sensitivity and specificity for identifying an exTEM hypocoagulable or hypercoagulable profile. An exTEM profile was arbitrarily considered abnormal if ≥2 of the measured parameters changed in the same direction (e.g, a shortened CT or CFT or an increased α‐angle or MCF to identify a hypercoagulable profile; or a prolonged CT or CFT or decreased α‐angle or MCF to identify a hypocoagulable profile) . According to the results of this previous study, G and TPI appeared to be the best indices for identifying hypercoagulable (AUC = 0.998 and AUC = 0.991, respectively) and hypocoagulable profiles (AUC = 0.987 and AUC = 0.999, respectively).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this previous study, the 4 measured parameters and 5 calculated indices (maximal clot elasticity, G, TPI, global index, and coagulation index) were evaluated to establish their sensitivity and specificity for identifying an exTEM hypocoagulable or hypercoagulable profile. An exTEM profile was arbitrarily considered abnormal if ≥2 of the measured parameters changed in the same direction (e.g, a shortened CT or CFT or an increased α‐angle or MCF to identify a hypercoagulable profile; or a prolonged CT or CFT or decreased α‐angle or MCF to identify a hypocoagulable profile) . According to the results of this previous study, G and TPI appeared to be the best indices for identifying hypercoagulable (AUC = 0.998 and AUC = 0.991, respectively) and hypocoagulable profiles (AUC = 0.987 and AUC = 0.999, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…A model‐based scoring system was developed in veterinary medicine, but the application of this scoring system was not possible in this study, because it used reference intervals for tests performed at 1 specific laboratory. Finally, no discard tube was used to collect the blood samples, unlike the recommended standard . It is possible that this method of blood collection led to preanalytical bias.…”
Section: Discussionmentioning
confidence: 99%
“…The results from TF‐TEG and TF + tPA‐TEG showed that experimentally inoculated dogs appeared hypercoagulable as compared with baseline as defined by a higher MA value and hypofibrinolytic as defined by a lower LY30 and LY60 and a higher CL30 and CL60 . Additional analyses were performed to compare week 3 results to those from subsequent time points, because it was unknown if doxycycline administration would affect TEG parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The velocity curve variables are generated from the TEG tracing and represent the first derivative of the associated waveform. These variables provide information regarding clot formation and clot breakdown . The MRTG reflects the maximal velocity of increase in clot strength and observed clot growth whereas TMRTG reflects the time interval required to reach maximal rate of clot formation .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many laboratories voluntarily participate in external proficiency testing, with recommendations for this testing being established by the American Society of Veterinary Clinical Pathology (23). Guidelines and consensus statements have been generated for several diagnostic activities, including reference interval establishment (24), prognostic markers in cancer (25), flow cytometric reporting in canine hematopoietic neoplasia (26), immunocytochemical staining (27), and viscoelastic-based hemostasis testing (28), to name a few examples. Similarly, cytologic (29) and histologic (30, 31) grading schemes have been proposed for various tumors.…”
Section: Consensus Statements and Standardization Of Testingmentioning
confidence: 99%